2018
DOI: 10.1038/s41598-018-24313-2
|View full text |Cite|
|
Sign up to set email alerts
|

Diversity and bioactive potential of culturable fungal endophytes of Dysosma versipellis; a rare medicinal plant endemic to China

Abstract: The plant Dysosma versipellis is known for its antimicrobial and anticancer properties but is a rare and vulnerable perennial herb that is endemic to China. In this study, 224 isolates were isolated from various tissues of D. versipellis, and were classified into 53 different morphotypes according to culture characteristics and were identified by sequence analyses of the internal transcribed spacer (ITS) region of the rRNA gene. Although nine strains were not assignable at the phylum level, 44 belonged to at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 78 publications
4
34
0
2
Order By: Relevance
“…The results showed that there was a speci c microbiome in 27 samples of tree medicinal licorices, and the relative abundance of endophytic fungi was correlated with the host plant species and root depth. For example, Ascomycota was the dominant phylum in all samples, followed by Basidiomycota, which result consistent with previous studies [48,49]. The phylum Ascomycota, as the largest phylum of fungi, has diverse populations and plays an important role in genetics [50], ecology [51] and phylogeny [52].…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that there was a speci c microbiome in 27 samples of tree medicinal licorices, and the relative abundance of endophytic fungi was correlated with the host plant species and root depth. For example, Ascomycota was the dominant phylum in all samples, followed by Basidiomycota, which result consistent with previous studies [48,49]. The phylum Ascomycota, as the largest phylum of fungi, has diverse populations and plays an important role in genetics [50], ecology [51] and phylogeny [52].…”
Section: Discussionsupporting
confidence: 90%
“…In addition to their interactions with plants, some members of Burkholderia have been shown to have an impact on fungal reproduction, and were suggested to be part of the mycorrhizal intracellular microbiome [9,73]. The genus Cadophora comprises several root endophytes with antimicrobial activity [74,75]. Cadophora species were also found to produce high levels of plant cell wall-degrading enzymes, as well as small, secreted proteins and aquaporins that typically function in tissue colonization and nutrient acquisition in the intercellular spaces of host plants [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Taxol, a widely employed anticancer drug, was originally isolated from the bark of Taxus brevifolia , and have also been produced by a series of endophytic fungi from different plants [ 12 , 13 ]. Tan et al isolated two endophytic fungi producing the podophyllotoxin, a main active compound from the host plant Dysosma versipellis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%